Influence of microemulsion components on transdermal delivery of immunomodulator glucosaminylmuramyl dipeptide - E. G. Kuznetsova; O. M. Kuryleva; L. A. Salomatina; S. V. Kursakov; S. V. Guryanova; V. I. Sevastyanov (Вестник трансплантологии и искусственных органов)
This paper demonstrates a chemical way of enhancing transdermal delivery using immunomodulator glucosaminylmuramyl dipeptide (GMDP) as an example. Objective: to study in vitro the effect of various components of the microemulsion composition on GMDP diffusion through the skin from a transdermal therapeutic system (TTS). Materials and methods. Medicinal substance – glucosaminylmuramyl dipeptide (Peptek, Russia). Excipients and raw materials: sodium chloride, purified water, sodium dodecyl sulfate, docusate sodium, oak bark, apricot kernel oil, alpha-tocopheryl acetate and Decaglyn PR-20 emulsifier. Equipment: Heidolph DIAX 900 mechanical disperser (Germany) and Hielscher UIS250V ultrasonic homogenizer (Germany). GMDP diffusion from TTS through unpreserved rabbit skin was studied on diffusion tester Copley (UK). GMDP in aqueous solutions was determined by reversed-phase high-performance liquid chromatography (RP-HPLC) on an Agilent 1200 chromatography system (Agilent Technologies, USA). Results. A microemulsion system composed of 20% docusate sodium in an oil phase and an oak bark decoction as an aqueous phase was developed. This made it possible to increase GMDP transdermal delivery by ~70% in comparison with the basic composition. Conclusion. The characteristic parameters of microemulsion components of GMDP contained in TTS, influencing GMDP diffusion through unpreserved rabbit skin in vitro, were determined. Introducing relative indicators would be advisable in order to correctly evaluate the results of different series of in vitro experiments with biological objects.